2D MoS2‐Based Nanomaterials for Therapeutic, Bioimaging, and Biosensing Applications. Issue 1 (22nd November 2018) - Yadav, Varnika; Roy, Shounak; Singh, Prem; Khan, Ziyauddin; Jaiswal, Amit
Abstract: Molybdenum disulfide (MoS2 ), a typical layered 2D transition metal dichalcogenide, has received colossal interest in the past few years due to its unique structural, physicochemical, optical, and biological properties. While MoS2 is mostly applied in traditional industries such as dry lubricants, intercalation agents, and negative electrode material in lithium‐ion batteries, its 2D and 0D forms have led to diverse applications in sensing, catalysis, therapy, and imaging. Herein, a systematic overview of the progress that is made in the field of MoS2 research with an emphasis on its different biomedical applications is presented. This article provides a general discussion on the basic structure and property of MoS2 and gives a detailed description of its different morphologies that are synthesized so far, namely, nanosheets, nanotubes, and quantum dots along with synthesis strategies. The biomedical applications of MoS2 ‐based nanocomposites are also described in detail and categorically, such as in varied therapeutic and diagnostic modalities like drug delivery, gene delivery, phototherapy, combined therapy, bioimaging, theranostics, and biosensing. Finally, a brief commentary on the current challenges and limitations being faced is provided, along with a discussion of some future perspectives for the overall improvement of MoS2 ‐based nanocomposites as a potential nanomedicine. Abstract : 2D MoS2 ‐based nanomaterials have emerged as a new class of material for biomedical applications. This review article discusses the growth of MoS2 as a nanomaterial in the field of biomedicine by highlighting its diverse applications in drug/gene delivery, phototherapy, imaging, sensing, and theranostics, which demonstrates the potential of this 2D material to evolve as a new class of nanomedicine.